Mutations in 16S rRNA that affect UGA (stop codon)-directed translation termination. - Göringer, H U (1991)
Site-directed mutagenesis was performed on a sequence motif within the 3' major domain of Escherichia coli 16S rRNA shown previously to be important for peptide chain termination. Analysis of stop codon suppression by the various mutants showed an exclusive response to UGA stop signals, which was correlated directly with the continuity of one or the other of two tandem complementary UCA sequences (bases 1199-1204). Since no other structural features of the mutated ribosomes were hampered and the translation initiation and elongation events functioned properly, we propose that a direct interaction occurs between the UGA stop codon on the mRNA and the 16S rRNA UCA motif as one of the initial events of UGA-dependent peptide chain termination. These results provide evidence that base pairing between rRNA and mRNA plays a direct role in termination, as it has already been shown to do for initiation and elongation.